Viral Pathogens, Risk Factors and Spatial Clustering of Porcine Respiratory Disease Complex in Hassan District of Karnataka State, India - Parameshwarappa, Satheesha Shettihally; Bhatt, Mudraje Narayana; Hiremath, Jagadish Basayya; Maheshwarappa, Yathish Hirenallur; Basavanthappa, Vedamurthy Kyathanahalli (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A pilot study was conducted to identify the prevailing viral agents associated with porcine respiratory disease complex, probable risk  factors and spatial clustering of these pathogens in Hassan district. A total of 225 blood samples were collected randomly from 27  different pig farms of the district. The detection of antibodies for viral pathogens like Porcine Circovirus 2 (PCV 2), Porcine Parvovirus  (PPV), Classical Swine Fever Virus (CSFV) and Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) was done using commercial  ELISA kits. An overall of 31.11 % samples were positive for viral co-seropositivity. The farm prevalence of viral co-seropositivity was  found to be 64 %. Among the co-seropositive samples, PPV and PCV 2 antibodies were found in 97.14 % and 94.28 %, respectively and  were appeared as dominant viral pathogens. The risk factors like large farm size, poor ventilation, movement of pigs between the pens,  exchange of live pigs between the farms, feedback type of feeding, visitors movements, inadequate watering, location of nearby farms,  high farm density, etc., were significantly influencing the higher occurrence of PRDC in the district. The analysis of spatial pattern of  PRDC in the district revealed no clustering of infection.
Keywords: Hassan; PRDC; Risk factors,; Seroprevalence; Spatial clustering.